Análisis del sistema de alumbrado público que da servicio en el barrio Zumbalica Centro, Cantón Latacunga, Provincia de Cotopaxi. Propuesta de sistema de alumbrado público más eficiente, en el periodo lectivo marzo 2 - abril 13 del 2016 - Anchatipan Aldaz, Robinson Santiago (2016)
The street lighting is a key component in the economy of a state and one of the important factors for productive and social development of the country. So you can´t stay without it, rather it should take appropriate measures for to have efficient systems and saving energy, for which required periodic evaluations of functioning of them, both in the energy sector and in the service; This project has main objective a study of the existing system of public lighting, which allows us to assess the quality of service and establish an optimal and energy efficient lighting, the current reality of the system of public lighting Zumbalica district center, the lighting is not suitable for use of roads as it does not have appropriate lighting levels in some cases the lamps do not have adequate or appropriate distances, determining that existing lamps are in poor condition and inconsistent with the types of lamps have been developed with new technologies.